Influenza vaccination coverage estimates in the fee-for service Medicare beneficiary population 2006 – 2016: Using population-based administrative data to support a geographic based near real-time tool. Issue 8 (3rd August 2018) - Shen, Angela K.; Warnock, Rob; Brereton, Stephaeno; McKean, Stephen; Wernecke, Michael; Chu, Steve; Kelman, Jeffrey A.
ABSTRACT: Older adults are at great risk of developing serious complications from seasonal influenza. We explore vaccination coverage estimates in the Medicare population through the use of administrative claims data and describe a tool designed to help shape outreach efforts and inform strategies to help raise influenza vaccination rates. This interactive mapping tool uses claims data to compare vaccination levels between geographic (i.e., state, county, zip code) and demographic (i.e., race, age) groups at different points in a season. Trends can also be compared across seasons. Utilization of this tool can assist key actors interested in prevention – medical groups, health plans, hospitals, and state and local public health authorities – in supporting strategies for reaching pools of unvaccinated beneficiaries where general national population estimates of coverage are less informative. Implementing evidence-based tools can be used to address persistent racial and ethnic disparities and prevent a substantial number of influenza cases and hospitalizations.